2017
DOI: 10.1038/s41598-017-05559-8
|View full text |Cite
|
Sign up to set email alerts
|

Environmental surveillance identifies multiple introductions of MRSA CC398 in an Equine Veterinary Hospital in the UK, 2011–2016

Abstract: Bacterial environmental and surgical site infection (SSI) surveillance was implemented from 2011–2016 in a UK Equine Referral Veterinary Hospital and identified 81 methicillin-resistant Staphylococcus aureus (MRSA) isolates. A cluster of MRSA SSIs occurred in early 2016 with the isolates confirmed as ST398 by multilocus sequence typing (MLST), which prompted retrospective analysis of all MRSA isolates obtained from the environment (n = 62), SSIs (n = 13) and hand plates (n = 6) in the past five years. Sixty fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 51 publications
0
27
0
1
Order By: Relevance
“…Scanning surveillance and other studies have reported the presence in the UK of LA-MRSA CC398, CC9, CC9/CC398 hybrid, CC22, CC30, CC130, CC705, and ST425 (Table 1). These isolates have been reported from horses (Loeffler et al, 2009; Bortolami et al, 2017), dairy cattle (Garcia-Alvarez et al, 2011; Paterson et al, 2012, 2014) beef cattle (Stone, 2017), poultry and pheasant (GOV. UK, 2013; Stone, 2017; Sharma et al, 2018), pigs (Hartley et al, 2014; Hall et al, 2015; Lahuerta-Marin et al, 2016; Sharma et al, 2016), pork meat (Dhup et al, 2015; Hadjirin et al, 2015; Fox et al, 2017), beef meat (Dhup et al, 2015), chicken and turkey meat (Dhup et al, 2015; Fox et al, 2017).…”
Section: La-mrsa In the United Kingdommentioning
confidence: 97%
See 1 more Smart Citation
“…Scanning surveillance and other studies have reported the presence in the UK of LA-MRSA CC398, CC9, CC9/CC398 hybrid, CC22, CC30, CC130, CC705, and ST425 (Table 1). These isolates have been reported from horses (Loeffler et al, 2009; Bortolami et al, 2017), dairy cattle (Garcia-Alvarez et al, 2011; Paterson et al, 2012, 2014) beef cattle (Stone, 2017), poultry and pheasant (GOV. UK, 2013; Stone, 2017; Sharma et al, 2018), pigs (Hartley et al, 2014; Hall et al, 2015; Lahuerta-Marin et al, 2016; Sharma et al, 2016), pork meat (Dhup et al, 2015; Hadjirin et al, 2015; Fox et al, 2017), beef meat (Dhup et al, 2015), chicken and turkey meat (Dhup et al, 2015; Fox et al, 2017).…”
Section: La-mrsa In the United Kingdommentioning
confidence: 97%
“…Further analysis of these two isolates by WGS indicated that they resembled other spa type 11 strains, clustering closely to another horse isolate from Belgium (Sharma et al, 2016). In a study from University of Liverpool, presence of LA-MRSA CC398 isolates, predominantly of spa -type 11 was reported from surveillance at an UK Equine Veterinary Hospital from 2011 to 2016; 65 of the 829 samples collected from environmental sites, surgical site implants and hand-plates were CC398 (Bortolami et al, 2017).…”
Section: Background Of Uk La-mrsa Isolatesmentioning
confidence: 99%
“…Despite the recognition of CC398 LA‐MRSA in neighbouring mainland Europe its epidemiology has been less well‐studied in the United Kingdom. Nonetheless, small numbers of CC398 MRSA isolates have been found, largely since 2012, from bovine milk (Paterson et al ), pigs (Hartley et al ; Hall et al ), poultry (Anonymous ), retail pork and poultry meat (Hadjirin et al ; Fox et al ), horses (Loeffler et al ; Bortolami et al ) and humans (Ward et al ; Harrison et al ; Kinross et al ) in the UK. Yet while clearly present in the UK and spread among different host species few data are available on the prevalence of CC398 MRSA in the UK human population.…”
Section: Introductionmentioning
confidence: 99%
“…Fatal cases of septicemia were also reported in Japan and Denmark ( 5 , 6 ). MRSA ST398 isolates from human postoperative surgical site infections were presented with complete genome sequencing in Canada and in a long-term MRSA surveillance study in the United Kingdom ( 7 , 8 ). The virulence potential of MRSA ST398 isolated from SSI has not been reported to date.…”
mentioning
confidence: 99%